Jordan : Teachers - World Bank (Washington, DC, 2014)
Jordan is a lower-middle-income country with a growing secondary school-aged population and a young, principally female teaching force based in urban areas. This eight policy goals includes the following headings: setting clear expectations for teachers; attracting the best into teaching; preparing teachers with useful training and experience; matching teachers' skills with students' needs; leading teachers with strong principals; monitoring teaching and learning; supporting teachers to improve instruction; and motivating teachers to perform.